2016
DOI: 10.4103/0971-5916.184302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid artery dynamics & correlation with cardiac & hepatic iron in β-thalassaemia patients

Abstract: Background & objectives:Early atherosclerosis and vascular complication have been described in thalassaemia patients. There is lack of data or guidelines regarding monitoring of vascular health in thalassaemia. This study was conducted to compare carotid artery structural and functional indices such as carotid artery intima-media thickness (CIMT), stiffness index (SI) and Young's elastic modulus (YEM) in β-thalassemia patients with age and sex matched controls, and to correlate these parameters with serum ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Clinical studies have shown increased PWV in iron‐overloaded patients due to β‐thalassaemia major (Detchaporn et al, ; Gedikli et al, ; Ulger, Aydinok, Gurses, Levent, & Ozyurek, ) or haemochromatosis (Cash et al, ). Furthermore, Valenti et al () identified an association between hyperferritinemia and aortic stiffness in hypertensive subjects, and Merchant et al () described that arterial stiffness increased significantly as cardiac iron‐overload increased in β‐thalassaemia patients receiving regular blood transfusions. On the other hand, Stakos et al () described that, in the absence of cardiac iron‐overload, patients with β‐thalassaemia major demonstrated aortic stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown increased PWV in iron‐overloaded patients due to β‐thalassaemia major (Detchaporn et al, ; Gedikli et al, ; Ulger, Aydinok, Gurses, Levent, & Ozyurek, ) or haemochromatosis (Cash et al, ). Furthermore, Valenti et al () identified an association between hyperferritinemia and aortic stiffness in hypertensive subjects, and Merchant et al () described that arterial stiffness increased significantly as cardiac iron‐overload increased in β‐thalassaemia patients receiving regular blood transfusions. On the other hand, Stakos et al () described that, in the absence of cardiac iron‐overload, patients with β‐thalassaemia major demonstrated aortic stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on transfusion-dependent thalassemia patients, carotid intimal media thickness (CIMT) and stiffness index (a marker for arterial wall resistance) were significantly higher than in controls (p < 0.001) with a significant correlation between CIMT and cardiac iron overload but not hepatic iron load. Moreover, they clas-sified the patients according to their age group and found that increasing age was associated with a greater increase in CIMT [24]. One study conducted on transfusion-independent TI also found an increase in CIMT compared to controls with a p value of 0.049 [25].…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Correlation was not supported in all studies, specifically, those where serum ferritin was compared with cardiac T2*, 28 adrenal T2*, 32 and carotid artery structure or vascular health. 33 Additionally, evidence from 1 study that investigated the relationships between changes in liver iron concentrations and changes in serum ferritin determined that serum ferritin nonresponse was associated with a decrease in liver iron concentrations in more than half of patients and concluded that the use of liver MRI may be particularly useful, as serum ferritin trends can be misleading. 34 Overall, given the low quality of evidence and absence of studies assessing reliability and responsiveness, strong conclusions on the use of serum ferritin levels cannot be made.…”
Section: Internal Validitymentioning
confidence: 99%